Noninvasive On-Skin Biosensors for Monitoring Diabetes Mellitus - Ali Sedighi; Tianyu Kou; Hui Huang; Yi Li (Nano-Micro Letters)
Highlights A comprehensive and critical evaluation of recent advances in sweat-based biochemical and physiological biomarkers for noninvasive diabetes monitoring. A novel emphasis on multimodal sensor integration—combining biochemical and physiological signals—to enhance accuracy, contextual awareness, and reliability in real-time diabetes management. A forward-looking analysis of AI-driven biosensing systems, standardized protocols, and regulatory and ethical frameworks enabling autonomous, secure, and personalized diabetes care.